Teachers’ Training Management Issues In the Hinterland Areas of Indonesia - Pohan, Albert Efendi; Koh, Lillian; Ghani, Muhammad Faizal Abd; Husna, Asmaul; Yanti, Fitri (Universitas Ahmad Dahlan, 2026)
Background/purpose. In Indonesia, teacher training programs have become a contemporary issue in every national curriculum reform because their implementation has not been consistently organized, especially in hinterland areas. Therefore, improving teachers’ competence should be organized sustainably through effective and efficient training management. This study investigates the current issues in teacher training management in the Hinterland Area. This research is important to conduct to obtain accurate information that can be used as positive input to the government in formulating new policies. Materials/methods. To achieve the research goals, the researchers used a qualitative approach with triangulation in the data analysis. Collecting data through online surveys and administered interviews with 3,140 teachers from the hinterland area in the Province of Riau Kepulauan, Indonesia. The observation was also organized to ensure the data was collected from surveys and administered interviews. Results. The study found: (1) Teacher training management includes planning, organizing, implementing, controlling, and evaluating. (2) These functions are not implemented effectively or efficiently. (3) The main problem is the implementation function, which is not uniform, fair, sustainable, or integrated with the needs of teachers in the hinterland area. (4) Teachers' competence is still low because they rarely attend the training program. Conclusion. Our findings make a significant contribution to the literature on teacher training management by highlighting the importance of effective and efficient management in improving teacher competence and education quality, particularly in hinterland areas. The findings support the theory of training management, emphasizing the need for planning, organizing, implementing, controlling, and evaluating training programs to achieve desired outcomes. This study paves the way for future research directions to develop a teacher-training management model based on hinterland areas.